A new type of aluminum alloy pipe joint material and its manufacturing process

CN123027490APending Publication Date: 2026-11-03JINGTIAN PRECISION TECHNOLOGY (HUIZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611441432.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing aluminum alloy pipe fitting materials struggle to balance strength, plasticity, and corrosion resistance. Brittle grain boundary phases make them susceptible to stress corrosion cracking, and traditional heat treatment processes have limitations in control, making it difficult to achieve a synergistic improvement in both strength and corrosion resistance.

Method used

Er-Zr composite microalloying was used to form a coherent Al3(Er,Zr) nanophase. Combined with Ce elements, a discontinuous Al-Ce intermetallic compound was formed at the grain boundaries, which divided the Mg2Si phase into an isolated island structure. A bimodal grain structure was formed by ultrasonic-assisted semi-solid extrusion and gradient cooling.

Benefits of technology

It achieves a synergistic improvement in the high strength, excellent plasticity and corrosion resistance of aluminum alloy pipe fitting materials, significantly improving stress corrosion resistance and fatigue life, and is suitable for harsh environments such as high-pressure hydraulic systems and aviation fuel pipelines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of aluminum alloy materials, and discloses a novel aluminum alloy pipe joint material and a manufacturing process thereof, which comprises a novel aluminum alloy pipe joint material, and the chemical components of the aluminum alloy pipe joint material comprise the following components in percentage by mass: Mg 0.7%-1.3%, Si 0.4%-0.9%, Cu 0.15%-0.35%, Mn 0.1%-0.3%, Er 0.06%-0.18%, Zr 0.12%-0.30%, Ce 0.04%-0.12%, Ti 0.03%-0.10%, and the balance is Al and inevitable impurities. The material matrix is diffusely distributed with coherent Al3(Er, Zr) nano phases with an average particle size of 3-12 nm, the Ce element is selectively segregated at the grain boundaries and forms discontinuously distributed Al-Ce intermetallic compounds, the Mg2Si phase is distributed in the form of isolated islands, and there is no continuous network of brittle phases at the grain boundaries. The preparation process comprises vacuum melting, ultrasonic-assisted semi-solid slurry preparation, semi-solid extrusion (gradient cooling at the outlet), solid solution water quenching and double-stage aging. The material has high strength, high plasticity and excellent corrosion resistance, and is suitable for manufacturing various high-performance aluminum alloy pipe joints.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy materials technology, specifically to a novel aluminum alloy pipe joint material and its manufacturing process. Background Technology

[0002] Aluminum alloy pipe fittings are widely used in aerospace, automotive manufacturing, petrochemical, marine engineering, and fluid transportation, with increasingly stringent requirements for their mechanical and corrosion resistance properties. Especially in harsh operating environments such as high-pressure hydraulic systems, aviation fuel pipelines, offshore platform pipelines, and thermal management systems for new energy vehicles, pipe fittings must not only withstand high internal pressure and alternating loads but also resist long-term corrosion from the working medium and environmental erosion. Their performance directly affects the safety and reliability of the entire pipeline system.

[0003] Currently, 6-series aluminum alloys (Al-Mg-Si series, such as 6061, 6082, 6063, etc.) are the mainstream materials for manufacturing aluminum alloy pipe fittings due to their good formability, weldability, and moderate strength. These alloys primarily achieve precipitation strengthening through the formation of metastable β″ phase (Mg5Si6) and equilibrium β phase (Mg2Si) by Mg and Si elements during aging. However, existing 6-series aluminum alloys have long faced a technical bottleneck in practical applications, where it is difficult to simultaneously improve strength, plasticity, and corrosion resistance. This bottleneck manifests in the following three aspects: Firstly, there is an inherent contradiction between strength and corrosion resistance. To improve strength, the content of Mg and Si elements is usually increased to increase the volume fraction of precipitated phases. However, supersaturated Mg and Si elements preferentially precipitate at grain boundaries, easily forming a continuous network of brittle Mg2Si phases. This continuous network structure weakens the grain boundary bonding force, making the material prone to intergranular fracture under stress and reducing plasticity. On the other hand, there is a potential difference between the continuous Mg2Si phase and the aluminum matrix, forming micro-galvanic corrosion channels in corrosive media, significantly increasing the susceptibility to stress corrosion cracking and intergranular corrosion. Especially in harsh environments containing chloride ions (such as marine atmospheres and de-icing salt), the intergranular corrosion problem caused by continuous grain boundary precipitates is more prominent, often resulting in brittle fracture under conditions far below the design stress.

[0004] Secondly, there is a trade-off between grain refinement and fatigue performance. To improve the strength and plasticity of alloys, the industry commonly uses grain refiners (such as Ti and Zr) to refine the casting microstructure and recrystallized grains. However, the crystallographic relationship between traditional grain refiners and the aluminum matrix has inherent flaws: Al3Ti and Al3Zr phases form incoherent or semi-coherent interfaces with the aluminum matrix, resulting in significant lattice mismatch (the mismatch between Al3Zr and Al is approximately 0.8%–1.2%, while Al3Ti's is even higher), and weak interfacial bonding. Although these incoherent phases can act as heterogeneous nucleation sites to refine the grains during solidification, stress concentration easily occurs at the interfaces between these phases and the matrix during subsequent heat treatment and service, becoming preferential sources of fatigue crack initiation, leading to a decrease in the material's fatigue strength and service life. This problem is particularly detrimental to pipe joints subjected to alternating loads, limiting their application in dynamically pressure-bearing structures.

[0005] Third, the limitations of conventional heat treatment regimes. Existing T5 and T6 heat treatment regimes (solution treatment + single-stage aging) have limited ability to control the precipitation behavior of Al-Mg-Si alloys. During single-stage aging, the type, size, and distribution of precipitates are difficult to control independently: to achieve high strength, higher aging temperatures or longer aging times are often required, but this leads to coarsening of the precipitates and a change from discontinuous to continuous grain boundary precipitates, sacrificing corrosion resistance; conversely, using lower aging temperatures to obtain better corrosion resistance fails to reach peak strength. This "one-sided" control dilemma makes it difficult for conventional heat treatment regimes to achieve a synergistic improvement in strength and corrosion resistance.

[0006] To address these issues, researchers have recently attempted improvements through microalloying and process innovation. For example, adding trace amounts of rare earth elements (a mixture of La, Ce, Pr, Nd, etc.) can purify the melt and refine the grains. However, existing technologies often use unseparated coarse rare earth elements, which are only used for melt purification and impurity removal, failing to actively control the morphology of grain boundary precipitates. Furthermore, while advanced processes such as spray forming, powder metallurgy, and intense plastic deformation can significantly improve strength, they are costly and difficult to mass-produce industrially. Moreover, ultrafine grain structures are often accompanied by decreased plasticity and poor thermal stability. In addition, attempts to improve the morphology of grain boundary precipitates through multi-stage aging or re-aging treatments have achieved some success, but they still cannot completely eliminate the formation of continuous Mg2Si networks at grain boundaries, limiting their effectiveness in improving stress corrosion cracking under extreme conditions.

[0007] Therefore, there is an urgent need to develop a novel aluminum alloy pipe joint material and its supporting manufacturing process that can fundamentally solve the aforementioned technical contradictions. This material should possess the following characteristics: a nano-reinforcing phase completely coherent with the aluminum matrix is ​​formed in the matrix to achieve efficient strengthening without introducing crack sources; an active modification mechanism exists at the grain boundaries, capable of dividing the continuous brittle Mg2Si network into isolated island structures to block corrosion channels; the microstructure exhibits a gradient distribution, with fine grains on the surface ensuring strength and wear resistance, and coarse grains in the core ensuring toughness and fatigue resistance. Simultaneously, the manufacturing process should be industrially feasible, enabling mass production using conventional equipment. This invention is proposed based on this technical requirement. Summary of the Invention

[0008] The purpose of this invention is to provide a new type of aluminum alloy pipe joint material and its manufacturing process, so as to solve the technical problem that it is difficult to balance the strength, plasticity and corrosion resistance of existing aluminum alloy pipe joint materials.

[0009] To achieve the above objectives, the present invention provides the following technical solution: A novel aluminum alloy pipe fitting material, the chemical composition of which, by mass percentage, includes: Mg 0.7%–1.3%, Si 0.4%–0.9%, Cu 0.15%–0.35%, Mn 0.1%–0.3%, Er 0.06%–0.18%, Zr 0.12%–0.30%, Ce 0.04%–0.12%, Ti 0.03%–0.10%, with the balance being Al and unavoidable impurities; the material matrix contains dispersed coherent Al3(Er,Zr) nanophases with an average particle size of 3–12 nm, Ce elements selectively segregate at grain boundaries to form discontinuously distributed Al-Ce intermetallic compounds, Mg2Si phases are distributed in isolated island-like distributions, and there is no continuous network of brittle Mg2Si phase at grain boundaries.

[0010] It is worth noting that this invention employs Er-Zr composite microalloying, utilizing Er and Zr to form an L12 structure Al3(Er,Zr) nanophase that is completely coherent with the aluminum matrix. The lattice mismatch is only about 0.5%, and the interfacial bonding force is much higher than that of traditional Al3Ti or Al3Zr phases. Thus, while achieving ultrafine grains, it does not become a crack source. At the same time, Ce element is introduced, and its selective segregation at grain boundaries is utilized to precipitate nanoscale Al-Ce intermetallic compounds in situ. This divides the continuous network brittle Mg2Si phase into isolated island structures, fundamentally eliminating the grain boundary embrittlement problem and achieving a synergistic improvement in strength and corrosion resistance.

[0011] Preferably, the chemical composition by mass percentage is: Mg 0.85%–1.15%, Si 0.55%–0.75%, Cu 0.20%–0.30%, Mn 0.15%–0.25%, Er 0.09%–0.15%, Zr 0.18%–0.24%, Ce 0.06%–0.10%, Ti 0.05%–0.08%, with the balance being Al and unavoidable impurities.

[0012] It is worth noting that this preferred composition range, while ensuring sufficient formation of the reinforcing phase, effectively suppresses the precipitation of coarse and brittle phases, enabling the material to obtain the best comprehensive mechanical properties and corrosion resistance.

[0013] Preferably, the mass ratio of Er to Zr is 1:1.5 to 1:2.5, and the volume fraction of Al3(Er,Zr) nanophase is 1.0% to 1.8%.

[0014] It is worth noting that controlling the specific ratio of Er to Zr can ensure that the Al3(Er,Zr) nanophase has the maximum coherent strengthening effect and thermal stability, and is not easily coarsened during subsequent high-temperature homogenization and extrusion processes, thereby maintaining a fine-grained structure.

[0015] Preferably, the average particle size of the Al-Ce intermetallic compound is 15–35 nm, and the volume fraction is 0.2%–0.5%; the average size of the isolated island-like Mg2Si phase is ≤60 nm, and the volume fraction is 5%–10%.

[0016] It is worth noting that the Al-Ce phase at this scale can effectively pin grain boundaries and divide the Mg2Si network without becoming a crack source due to its excessive size; the divided island-like Mg2Si phase significantly reduces the connectivity of grain boundary corrosion channels, thereby greatly improving the stress corrosion resistance.

[0017] Preferably, the impurity content of the aluminum alloy pipe fitting material meets the following requirements: Fe≤0.15%, Zn≤0.10%, Ni≤0.05%, other individual impurities≤0.03%, and total impurities≤0.25%.

[0018] It is worth noting that strictly controlling the content of harmful impurities such as Fe, Zn, and Ni can prevent the formation of coarse iron-containing phases or low-melting-point eutectic phases, thus preventing their adverse effects on the plasticity and corrosion resistance of materials.

[0019] Preferably, the material has a bimodal grain structure consisting of a fine-grained region and a coarse-grained region, wherein the average grain size of the fine-grained region is 2 to 6 μm, the average grain size of the coarse-grained region is 12 to 20 μm, and the area ratio of the fine-grained region to the coarse-grained region is 1:1.2 to 1:2.3.

[0020] It is worth noting that the bimodal grain structure is a unique microstructure of this process: the fine-grained region provides high strength and high wear resistance, while the coarse-grained region provides good plasticity and toughness. The two work together to enable the material to achieve excellent elongation while maintaining high strength.

[0021] Preferably, in the bimodal grain structure, the volume fraction of the fine-grained region is 30%–45%, the volume fraction of the coarse-grained region is 55%–70%, and the overall average grain size of the material is 5–9 μm.

[0022] It is worth noting that by controlling the gradient cooling parameters, the volume fraction and overall grain size of the bimodal structure can be precisely adjusted, thereby customizing the comprehensive mechanical properties of the pipe fitting as needed.

[0023] Preferably, the Al3(Er,Zr) nanophase has an L12 type ordered crystal structure, maintains a completely coherent interface with the aluminum matrix, and the lattice mismatch between the two is 0.4% to 0.6%.

[0024] It is worth noting that this crystal structure and mismatch range can achieve optimal coherent strengthening effect and interface stability: the L12 type ordered structure is highly matched with the aluminum matrix lattice, and the extremely low mismatch ensures strong phase interface bonding force, preventing interface stress concentration from becoming a source of fatigue crack initiation, which is different from the defect of traditional non-coherent refinement phases that are prone to fatigue failure; at the same time, the dispersed coherent nanophase can effectively pin dislocations and subgrain boundaries, significantly improving the matrix strength without interrupting the continuity of plastic deformation, and has excellent resistance to coarsening at high temperatures. It can maintain the stability of the structure during heat treatment and long-term service, taking into account the strength, plasticity and fatigue resistance of the material.

[0025] Preferably, the bimodal grain structure exhibits a gradient distribution along the wall thickness direction of the pipe joint: the outer surface area of ​​the pipe joint is a fine-grained region, while the central core area is a coarse-grained region, with the grain size increasing from the surface to the interior.

[0026] It is worth noting that this gradient structure can achieve differentiated performance adaptation in the wall thickness direction of the pipe joint: the fine-grained region on the surface can significantly improve the surface strength, hardness and wear resistance of the material, inhibit the penetration of corrosive media and the initiation of fatigue cracks, and adapt to the harsh service environment of the outer surface of the pipe joint; the coarse-grained region in the core retains excellent plasticity and toughness, which can buffer internal pressure impact, absorb deformation energy, and hinder crack propagation; the gradient transition grain structure avoids the shortcomings of insufficient plasticity of single fine grains and low strength of single coarse grains, so that the pipe joint has the comprehensive advantages of surface corrosion and wear resistance and core high toughness and crack resistance under pressure conditions, thereby improving the overall service reliability.

[0027] This invention also provides a process for preparing the above-mentioned aluminum alloy pipe joint material, comprising the following steps: weighing pure aluminum and each intermediate alloy according to the proportion, and preparing the material under a vacuum degree ≥3×10⁻⁶. -3Melting is carried out at Pa and temperature of 730–760℃, with electromagnetic stirring for 10–15 minutes. Then, argon gas with a purity ≥99.99% is introduced for rotary blowing degassing and refining. The melt is then cooled to 600–615℃ and subjected to ultrasonic vibration with a power of 600–1200W for 6–10 minutes to obtain a semi-solid slurry with a solid fraction of 45%–55%. The semi-solid slurry is directly transferred to a mold preheated to 250–280℃ and extruded at an extrusion ratio of 16–22:1. Semi-solid extrusion is used to obtain tube blanks, and gradient cooling is adopted at the extrusion outlet: water mist cooling (50-80℃ / s) on the outer surface of the tube blank and compressed air cooling (20-30℃ / s) on the inner hole; after solution treatment at 525-545℃ for 1-1.5 hours, the tube blanks are immediately transferred to water at 20-40℃ for water quenching; then pre-aging at 125-135℃ for 3-5 hours, and finally final aging at 170-180℃ for 7-9 hours, followed by air cooling to room temperature.

[0028] It is worth noting that the core innovation of this process lies in: ultrasonic vibration breaking up the primary phase and promoting melt homogenization to obtain high-quality semi-solid slurry; semi-solid extrusion combined with outlet gradient cooling to form a temperature gradient from the surface to the inside in the thickness direction of the billet, thereby inducing the formation of a bimodal grain structure; and two-stage aging to precisely control the type, size and distribution of precipitated phases, so that the coherent Al3(Er,Zr) phase and metastable β″ phase can fully exert their strengthening effect, while avoiding the precipitation of coarse equilibrium phases.

[0029] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention effectively overcomes the technical bottleneck of simultaneously improving the strength, plasticity, and corrosion resistance of traditional 6-series aluminum alloys through the synergistic effect of Er-Zr coherent nanophase strengthening and Ce grain boundary modification. The material has a room temperature tensile strength ≥370MPa, yield strength ≥330MPa, elongation ≥15%, Brinell hardness ≥105HB, uniform corrosion rate ≤0.028mm / a after immersion in 3.5wt% sodium chloride aqueous solution at room temperature for 72 hours, and stress corrosion cracking threshold ≥260MPa. Its comprehensive performance is significantly better than that of conventional 6061-T6 aluminum alloy. 2. This invention uses ultrasonic-assisted semi-solid extrusion combined with gradient cooling process to obtain a controllable bimodal grain structure in aluminum alloy pipe joints for the first time. The fine grain region on the surface improves wear resistance and fatigue resistance, while the coarse grain region in the core ensures toughness, thus realizing the gradient design of material properties. 3. The entire process of this invention is free of organic solvent pollution and produces little waste liquid, meeting the requirements of green manufacturing. Furthermore, through rotary jet degassing refining and ultrasonic treatment, the porosity and inclusions in the ingot are significantly reduced, improving the density of the material and the yield. 4. The materials and processes of this invention are universal and can be extended to the manufacture of other 6-series aluminum alloy products, providing a brand-new technical path for the development of high-performance aluminum alloy structural components. Detailed Implementation

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] To address the technical challenges in existing aluminum alloy pipe joint materials—namely, the difficulty in balancing strength, plasticity, and corrosion resistance, as well as the sensitivity to stress corrosion cracking caused by brittle grain boundary phases—the following technical solution is proposed.

[0032] Example 1 This embodiment provides a novel aluminum alloy pipe joint material and its manufacturing process.

[0033] The chemical composition of the aluminum alloy pipe fitting material in this embodiment, by mass percentage, is as follows: Mg 1.0%, Si 0.7%, Cu 0.25%, Mn 0.20%, Er 0.12%, Zr 0.20%, Ce 0.08%, Ti 0.06%, with the balance being Al and unavoidable impurities. Impurity content: Fe 0.12%, Zn 0.08%, Ni 0.03%, individual other impurities ≤0.02%, total impurities ≤0.20%.

[0034] The preparation process includes the following steps: (1) Weigh pure aluminum and aluminum-silicon, aluminum-magnesium, aluminum-copper, aluminum-manganese, aluminum-zirconium, aluminum-erbium, aluminum-cerium, and aluminum-titanium master alloys, place them in a vacuum induction melting furnace, and evacuate to a vacuum degree ≥3×10 -3 Pa, heated to 745℃ to melt, electromagnetically stirred for 12 minutes, then argon gas with a purity ≥99.99% was introduced for rotary blowing degassing and refining, and then left to stand for 10 minutes to remove slag.

[0035] (2) Cool the melt to 608°C and apply ultrasonic vibration with a power of 900W and a frequency of 20kHz for 8 minutes to obtain a semi-solid slurry with a solid fraction of about 50% and an average solid particle size of ≤25μm.

[0036] (3) The semi-solid slurry is directly transferred to the pipe joint extrusion die preheated to 265°C and semi-solid extrusion is carried out at an extrusion ratio of 18:1 and an extrusion speed of 0.10m / s. Gradient cooling is adopted at the extrusion outlet: water mist cooling on the outer surface of the pipe blank (cooling rate 65°C / s) and compressed air cooling on the inner hole (cooling rate 25°C / s) to obtain the pipe blank.

[0037] (4) The tube blank is solution treated at 535℃ for 1.2 hours and then immediately transferred to water quenching at 30℃.

[0038] (5) Perform two-stage aging: First, pre-age at 130℃ for 4 hours, then increase the temperature to 178℃ at a rate of 4℃ / min for final aging for 8 hours. After the aging is completed, remove the product and air-cool it to room temperature.

[0039] Microstructure observation and performance testing were performed on the aluminum alloy pipe joint prepared in this embodiment: The matrix contained dispersed Al3(Er,Zr) nanophases with an average particle size of 8 nm and an ordered L12 crystal structure. This phase maintained a completely coherent interface with the aluminum matrix, with a lattice mismatch of approximately 0.5% and a volume fraction of approximately 1.5%. At the grain boundaries, the Al-Ce intermetallic compound had an average particle size of 25 nm and a volume fraction of approximately 0.35%. The Mg2Si phase was distributed in isolated island-like patterns, with an average size ≤50 nm and a volume fraction of approximately 7%. The bimodal grain structure exhibited a gradient distribution along the pipe blank wall thickness: the outer surface region was a fine-grained region with an average grain size of 4 μm; the central core region was a coarse-grained region with an average grain size of 16 μm. The grain size generally increased from the surface to the interior, with a fine-grained region to coarse-grained region area ratio of approximately 1:1.8, and an overall average grain size of 7 μm. In this embodiment, the pipe fitting is used in aircraft hydraulic system piping, employing a standard flared connection. The working medium is aviation hydraulic oil (Skydrol LD-4), and the operating temperature is -55℃ to 135℃. Simulated flight condition testing showed that the fitting exhibited no leakage after 5000 pressure cycles at a working pressure of 21MPa, achieving a fatigue life of 5.2 × 10⁻⁶. 6 The cycle life is 42% higher than that of the same specification 6061-T6 connector, and the weight is only 2.71g / cm². 3 Compared to steel joints, it reduces weight by approximately 62%, verifying its applicability and lightweight effect in aviation hydraulic pressure pipelines.

[0040] Example 2 The difference between this embodiment and Embodiment 1 is that the chemical composition adopts the preferred range of claim 2: Mg 0.85%, Si 0.55%, Cu 0.20%, Mn 0.15%, Er 0.09%, Zr 0.18%, Ce 0.06%, Ti 0.05%, with the balance being Al and unavoidable impurities. Impurity content: Fe 0.10%, Zn 0.06%, Ni 0.02%, total impurities ≤0.18%.

[0041] The process parameters were adjusted accordingly as follows: melting temperature 735℃, semi-solid slurry preparation temperature 605℃, ultrasonic power 700W, extrusion ratio 17:1, solution temperature 530℃, pre-aging 125℃×4h, final aging 175℃×8h, and gradient cooling parameters were the same as in Example 1.

[0042] Microstructural observation of the aluminum alloy pipe joint prepared in this embodiment revealed the following: The matrix contained dispersed Al3(Er,Zr) nanophases of an L12-type ordered crystal structure with an average particle size of 7 nm. This phase maintained a completely coherent interface with the aluminum matrix, exhibiting a lattice mismatch of approximately 0.45% and a volume fraction of approximately 1.2%. At the grain boundaries, Al-Ce intermetallic compounds had an average particle size of 22 nm and a volume fraction of approximately 0.28%. The Mg2Si phase was distributed in isolated island-like formations with an average size ≤45 nm. The bimodal grain structure exhibited a gradient distribution along the pipe blank wall thickness: the average grain size in the fine-grained region on the outer surface was 3 μm, while the average grain size in the coarse-grained region of the core was 14 μm. The grain size increased from the surface inwards, with a fine-grained region to coarse-grained region area ratio of approximately 1:1.5. The overall average grain size of the material was 6 μm. This material was used in aviation fuel system pipe joints and assembled into RP-3 aviation kerosene pipelines using a fusion welding connection method. After 1,000 hours of fuel immersion, the tensile strength retention rate of the joint reached 96.2%, the stress corrosion threshold was still 260 MPa, and there was no obvious softening in the weld heat-affected zone. This indicates that the material has both high corrosion resistance and heat decay resistance in fuel medium, and is suitable for long-term service of wing fuel tanks and engine fuel supply lines.

[0043] Example 3 The difference between this embodiment and Embodiment 1 is that the chemical composition adopts another preferred range of claim 2: Mg 1.15%, Si 0.75%, Cu 0.30%, Mn 0.25%, Er 0.15%, Zr 0.24%, Ce 0.10%, Ti 0.08%, with the balance being Al and unavoidable impurities. Impurity content: Fe 0.14%, Zn 0.09%, Ni 0.04%, total impurities ≤ 0.24%.

[0044] The process parameters were adjusted accordingly as follows: melting temperature 755℃, semi-solid slurry preparation temperature 612℃, ultrasonic power 1100W, extrusion ratio 21:1, solution temperature 542℃, pre-aging 132℃×5h, and final aging 182℃×7h.

[0045] Microstructural observation of the aluminum alloy pipe joint prepared in this embodiment revealed the following: The matrix contained dispersed Al3(Er,Zr) nanophases of an L12-type ordered crystal structure with an average particle size of 9 nm. This phase maintained a completely coherent interface with the aluminum matrix, exhibiting a lattice mismatch of approximately 0.55% and a volume fraction of approximately 1.7%. At the grain boundaries, Al-Ce intermetallic compounds had an average particle size of 30 nm and a volume fraction of approximately 0.45%. The Mg2Si phase was distributed as isolated islands with an average size ≤55 nm. The bimodal grain structure exhibited a gradient distribution along the pipe blank wall thickness: the average grain size in the fine-grained region on the outer surface was 5 μm, while the average grain size in the coarse-grained region at the core was 18 μm. The grain size increased from the surface inwards, with a fine-grained region to coarse-grained region area ratio of approximately 1:2.1. The overall average grain size of the material was 8 μm. This material was used in the high-pressure pipe joint of an aircraft landing gear retraction mechanism, installed using a compression fitting method. Simulated landing gear retraction and extension impact test (peak stress 350MPa, frequency 1Hz, 10 cycles) 4 After ( ) times, no cracks appeared in the joint, and the permanent deformation was ≤0.08mm, proving that its fatigue resistance and dimensional stability under high impact load are reliable and meet the design requirements of key dynamic pressure-bearing structures in aviation.

[0046] Comparative Example 1 (Prior Art) This comparative example uses commercially available 6061-T6 aluminum alloy pipe fitting material, without the addition of Er, Zr, and Ce elements. Its chemical composition (mass percentage) is: Mg 0.9%, Si 0.6%, Cu 0.25%, Mn 0.15%, Cr 0.2%, with the balance being Al and unavoidable impurities (Fe≤0.7%).

[0047] The preparation process adopts the traditional process: semi-continuous casting → homogenization annealing (560℃×12h) → hot extrusion (500℃, extrusion ratio 18:1) → solution treatment (540℃×1h, water quenching) → single-stage aging (175℃×8h, air cooling).

[0048] Microstructure observation of the comparative material: There is no Al3(Er,Zr) nanophase in the matrix, and the Mg2Si phase is distributed in a continuous network at the grain boundaries; the grains are a single coarse grain structure with no gradient distribution of bimodal grain structure, and the overall average grain size is about 25 μm.

[0049] Comparative Example 2 (without Ce grain boundary modification) The difference between this comparative example and Example 1 is that Ce element is not added, while the remaining chemical composition and preparation process are exactly the same as in Example 1.

[0050] Microstructure observation of the comparative material revealed the presence of L12-type coherent Al3(Er,Zr) nanophases in the matrix; absence of Al-Ce intermetallic compounds at grain boundaries, with the Mg2Si phase exhibiting a discontinuous network distribution; and a bimodal grain structure, although the brittle grain boundary phases were not effectively separated.

[0051] Comparative Example 3 (No Gradient Cooling) The difference between this comparative example and Example 1 is that the extrusion outlet uses overall water cooling (cooling rate 65℃ / s) instead of gradient cooling, while the remaining chemical composition and preparation process are exactly the same as in Example 1.

[0052] Microstructure observation of the comparative material: L12 type coherent Al3(Er,Zr) nanophase exists in the matrix, and Mg2Si phase is distributed in isolated islands at the grain boundaries; the grains are a single fine-grained structure with no gradient distribution characteristics in the wall thickness direction, and the overall average grain size is about 5μm.

[0053] Performance Testing and Comparison The aluminum alloy materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested according to national standards. Tensile properties were tested according to GB / T 228.1-2021 "Metallic materials – Tensile testing – Part 1: Test method at room temperature"; Brinell hardness was tested according to GB / T 231.1-2018 "Metallic materials – Brinell hardness testing – Part 1: Test method"; uniform corrosion rate was tested using a 3.5wt% sodium chloride aqueous solution immersion method for 72 hours; stress corrosion cracking threshold was tested using the slow strain rate tensile method (SSRT). The results are as follows: Table 1 Comparison of Core Components and Process Parameters

[0054] Table 2 Comparison of Microstructure and Properties

[0055] As clearly shown in Tables 1 and 2, the overall performance of Examples 1-3 of this invention is significantly superior to that of Comparative Example 1. In aerospace applications, this material has been validated through various joining processes, including flaring, extrusion, and welding. In terms of application performance, its stress corrosion cracking threshold is increased by more than 116% compared to Comparative Example 1, its tensile strength is increased by more than 21%, and its elongation is ≥15.5%. These indicators meet or exceed the performance requirements of the aerospace standard AMS 4165 for pipe fittings, indicating that this material can simultaneously meet the service requirements of high strength, high toughness, and stress corrosion resistance in aircraft hydraulic, fuel, and environmental control pipelines, effectively extending maintenance cycles and improving flight safety.

[0056] Comparing Example 1 and Comparative Example 2, it can be seen that the grain boundary modification effect of Ce is the key to improving the stress corrosion resistance under aviation service conditions. When Ce is missing, even with the retention of Er-Zr composite reinforcement, the stress corrosion cracking threshold still decreases by about 35%, indicating that Ce is indispensable for blocking grain boundary corrosion channels and ensuring the long-term safety of aviation fuel and hydraulic pipelines in humid / salt environments.

[0057] Comparing Example 1 and Comparative Example 3, it can be seen that the bimodal grain structure formed by gradient cooling is a key process method to achieve the synergy of high strength and high plasticity. Without gradient cooling, the elongation decreases by about 19%, which will weaken the toughness reserve of aerospace pipe joints under impact loads. This shows that the process has important engineering significance for the reliability design of aerospace dynamic pressure-bearing structural components.

[0058] In summary, the materials and processes disclosed in the various embodiments of this invention have been verified through a variety of typical aviation connection methods (flared, extruded, and welded). Their comprehensive performance covers the main pipe joint application scenarios such as aircraft hydraulic systems, fuel lines, landing gear, and environmental control systems, and the effects are clear—fatigue life, stress corrosion resistance, and lightweighting are all significantly better than existing commonly used aviation aluminum alloys, and they have direct engineering transformation and airworthiness application value.

[0059] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A novel aluminum alloy pipe joint material, characterized in that, The chemical composition of the aluminum alloy pipe joint material, by mass percentage, includes: Mg 0.7%–1.3%, Si 0.4%–0.9%, Cu 0.15%–0.35%, Mn 0.1%–0.3%, Er 0.06%–0.18%, Zr 0.12%–0.30%, Ce 0.04%–0.12%, Ti 0.03%–0.10%, with the balance being Al and unavoidable impurities. The material matrix contains a coherent Al3(Er,Zr) nanophase with an average particle size of 3–12 nm. Ce elements selectively agglomerate at the grain boundaries to form discontinuous Al-Ce intermetallic compounds. The Mg2Si phase is distributed in isolated island-like patterns, and there is no continuous network of brittle Mg2Si phase at the grain boundaries.

2. The novel aluminum alloy pipe joint material according to claim 1, characterized in that, The chemical composition, by mass percentage, is as follows: Mg 0.85%–1.15%, Si 0.55%–0.75%, Cu 0.20%–0.30%, Mn 0.15%–0.25%, Er 0.09%–0.15%, Zr 0.18%–0.24%, Ce 0.06%–0.10%, Ti 0.05%–0.08%, with the balance being Al and unavoidable impurities.

3. The novel aluminum alloy pipe joint material according to claim 1, characterized in that, The mass ratio of Er to Zr is 1:1.5 to 1:2.5, and the volume fraction of Al3(Er,Zr) nanophase is 1.0% to 1.8%.

4. The novel aluminum alloy pipe joint material according to claim 1, characterized in that, The average particle size of Al-Ce intermetallic compounds is 15–35 nm, and the volume fraction is 0.2%–0.5%; the average size of isolated island-like Mg2Si phases is ≤60 nm, and the volume fraction is 5%–10%.

5. The novel aluminum alloy pipe joint material according to claim 1, characterized in that, The impurity content of aluminum alloy pipe fitting materials shall meet the following requirements: Fe≤0.15%, Zn≤0.10%, Ni≤0.05%, other individual impurities≤0.03%, and total impurities≤0.25%.

6. The novel aluminum alloy pipe joint material according to claim 1, characterized in that, The material has a bimodal grain structure consisting of a fine-grained region and a coarse-grained region, wherein the average grain size of the fine-grained region is 2-6 μm, the average grain size of the coarse-grained region is 12-20 μm, and the area ratio of the fine-grained region to the coarse-grained region is 1:1.2-1:2.

3.

7. The novel aluminum alloy pipe joint material according to claim 6, characterized in that, In the bimodal grain structure, the volume fraction of the fine-grained region is 30%–45%, the volume fraction of the coarse-grained region is 55%–70%, and the overall average grain size of the material is 5–9 μm.

8. The novel aluminum alloy pipe joint material according to claim 1, characterized in that, The Al3(Er,Zr) nanophase has an L12 type ordered crystal structure and maintains a completely coherent interface with the aluminum matrix, with a lattice mismatch of 0.4% to 0.6%.

9. A novel aluminum alloy pipe joint material according to claim 6, characterized in that, The bimodal grain structure exhibits a gradient distribution along the wall thickness of the pipe joint: the outer surface area of ​​the pipe joint is a fine-grained region, while the central core area is a coarse-grained region, with the grain size generally increasing from the surface to the interior.

10. A process for preparing the aluminum alloy pipe joint material according to any one of claims 1 to 9, characterized in that, The process includes the following steps: Weigh pure aluminum and each intermediate alloy according to the specified ratio, and then heat them under a vacuum of ≥3×10⁻⁶. -3 Melting is carried out at Pa and temperature of 730–760℃, with electromagnetic stirring for 10–15 minutes. Then, argon gas with a purity ≥99.99% is introduced for rotary blowing degassing and refining. The melt is then cooled to 600–615℃ and subjected to ultrasonic vibration with a power of 600–1200W for 6–10 minutes to obtain a semi-solid slurry with a solid fraction of 45%–55%. The semi-solid slurry is directly transferred to a mold preheated to 250–280℃ and extruded at an extrusion ratio of 16–22:

1. Semi-solid extrusion is used to obtain tube blanks, and gradient cooling is adopted at the extrusion outlet: water mist cooling (50-80℃ / s) on the outer surface of the tube blank and compressed air cooling (20-30℃ / s) on the inner hole; after solution treatment at 525-545℃ for 1-1.5 hours, the tube blanks are immediately transferred to water at 20-40℃ for water quenching; then pre-aging at 125-135℃ for 3-5 hours, and finally final aging at 170-180℃ for 7-9 hours, followed by air cooling to room temperature.